The Paradox of ESG Performance and Audit Fees in the Energy Sector: Mediating and Moderating Effects of Green Innovation, Supply Chain Management, and Media Attention - Zhang, Wanlin; Yin, Shi (International Journal of Mass Communication, 2025)
The ESG concept, which covers the dimensions of corporate environment, society, and corporate governance, has promoted the transformation of corporate goals from pursuing maximum self-interest to balancing environmental, social, and corporate governance values. The vast majority of current research focuses on how improving corporate ESG performance can reduce audit fees, and there is little literature specifically studying the relationship between ESG performance and audit fees for energy industry companies. This article takes energy-listed companies from 2018 to 2022 as samples to analyze the impact of ESG performance and its environmental, social, and corporate governance dimensions on audit fees in the energy industry. At the same time, this study explores whether ESG performance and its environmental, social, and corporate governance dimensions have an intermediary mechanism for audit fees through green innovation capabilities, supply chain integration management, and shareholder equity, as well as the moderating effect of media attention on the relationship between ESG performance, environmental, social, and corporate dimensions and audit fees. Research has found that: (1) the improvement of ESG performance, environmental performance, social performance, and corporate governance performance of energy companies cannot reduce audit fees; (2) Green innovation capability and supply chain integrated management play an intermediary role between corporate ESG performance and audit fees, supply chain integrated management and shareholder equity play an intermediary role between corporate environmental performance and audit fees, green innovation capability and supply chain integrated management play an intermediary role between corporate social performance and audit fees, and green innovation capability plays an intermediary role between corporate governance performance and audit fees; (3) Media attention has played a positive moderating role in the impact of corporate ESG performance and environmental dimensions on audit fees. The research has improved the ESG performance of energy industry enterprises in specific industries and the relationship between their performance in the environmental, social, and governance dimensions and audit fees. This will further promote energy enterprises to practice ESG concepts and achieve sustainable development.